The Effect of Tamarind Fruit Nanoparticles (Tamarindus indica) on the Sperm Quality of Hyperglycemic Rats - Bagus Hammam Falah; Wulan Christijanti; Nugrahaningsih WH; R. Susanti (Life Science, 2025)
Hyperglycemia is an increase in glucose levels in the blood. This condition can trigger glucose autooxidation which can produce free radicals. Free radicals can cause damage to male reproductive organs and quality. Tamarind fruit has a high flavonoid which has the potential as an antioxidant. This study aims to analyze the effect of tamarind fruit nanoparticles on spermatozoa quality in hyperglycemic rats. This study is experimental with Post-Test Control Group Design. A sample of 15 male Wistar rats were induced by alloxan and then divided into three groups, namely the control group, tamarind fruit nanoparticles with a dose of 30 mg/KgBB (NP1) and 60 mg/KgBB (NP2) for 28 days. Sperm quality was observed with parameters of concentration, motility and viability. The data were analyzed using One Way ANOVA and LSD. The results of the Anova test showed that tamarind nanoparticle treatment could significantly improve sperm quality (P<0.05). The LSD test showed that the concentration, motility and viability of sperm in group (K) were significantly different from groups NP1 and NP2. The highest to lowest average sperm concentration in sequence was in groups NP2 (49.60x106±6.06x106), NP1 (41.60x106±7.40x106) and K (20.80x106±7.56x106). The highest to lowest average percentage of sperm motility in sequence was in groups NP2 (82.20±9.75), NP1 (74.00±4.74), K (47.20±10.66). The highest to lowest average percentage of sperm viability in sequence was in the NP2 group (76.80±4.49), NP1 (72.20±7.12), K (31.60±7.89). The conclusion of this study is that tamarind nanoparticles have an effect on improving sperm quality in hyperglycemic rats.